Lactiplantibacillus plantarum J‐15 reduced calcium oxalate kidney stones by regulating intestinal microbiota, metabolism, and inflammation in rats. Issue 6 (7th May 2022) - Tian, Lei; Liu, Yu; Xu, Xiaofang; Jiao, Pengrui; Hu, Gaofei; Cui, Yaqian; Chen, Jixiang; Ma, Yucheng; Jin, Xi; Wang, Kunjie; Sun, Qun
Abstract: The prevention role of Lactiplantibacillus plantarum against the formation of kidney stones has been increasingly recognized; its mechanism, however, has mainly been focused on inhibiting the inflammation in the colon in the gastrointestinal (GI) system, and the intestinal metabolites from microflora have not been revealed fully with regarding to the stone formation. In this study, we investigated the effect of L . plantarum J‐15 on kidney stone formation in renal calcium oxalate (CaOx) rats induced by ethylene glycol and monitored the changes of intestinal microflora and their metabolites detected by 16S rRNA sequencing and widely targeted analysis, followed by the evaluation of the intestinal barrier function and inflammation levels in the colon, blood and kidney. The results showed that L . plantarum J‐15 effectively reduced renal crystallization and urinary oxalic acid. Ten microbial genera, including anti‐inflammatory and SCFAs‐related Faecalibaculum, were enriched in the J‐15 treatment group. There are 136 metabolites from 11 categories significantly different in the J‐15 supplementation group compared with CaOx model rats, most of which were enriched in the amino acid metabolic and secondary bile acid pathways. The expression of intestinal tight junction protein Occludin and the concentration of pro‐inflammatory cytokines and prostaglandin were decreased in the intestine, which further reduced the translocated lipopolysaccharide and inflammation levels in the blood upon J‐15 treatment. Thus, the inflammation and injury in the kidney might be alleviated by downregulating TLR4/NF‐κB/COX‐2 signaling pathway. It suggested that L . plantarum J‐15 might reduce kidney stone formation by restoring intestinal microflora and metabolic disorder, protecting intestinal barrier function, and alleviating inflammation. This finding provides new insights into the therapies for renal stones.